PENERAPAN PEMBELAJARAN IPA TERPADU MENGGUNAKAN MODEL WEBBED UNTUK MENINGKATKAN LITERASI SAINS SISWA PADA TEMA KALOR DAN PERUBAHAN SUHU - Herni Suryaneza (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The integrated science learning using webbed model was done to increase student science literacy in heat and temperature changes theme. The research was done to learn the effectiveness of the model on using quasi experiment method with non-randomized subject pretest posttest control group design.The subjects were two class of science learning of grade VII from one of junior high school at Cirebon District, West Java, Indonesia. The student in control class were  taught on using non integrated way. The instrument used were written test, observation sheet, questionnaire and interview guidance. The research shows that learning science through integrated increase science literacy of students, significantly better than control class. The significantly enhancement was also shows in both of content and process aspects. Moreover, integrated in learning science can build positive attitudes of student.Keyword :1. integrated science, 2.learning webbed models, 3. students science literacy.